The role of artificial intelligence in the development of cognitive level of social science students - امین, د. شنۆ دەرویش محمد (Sulaimani Journal for Humanities, 2025)
The study aimed to identify the role of artificial intelligence in cognitive development among social sciences students and its relationship to variables such as gender and educational level. To achieve this goal, a descriptive analytical approach was used, fully aligned with the research objectives. The research population consists of (322) male and female students in the Social Sciences Department for the academic year (2024-2025). The research tool is a questionnaire consisting of (33) items. After validation and reliability of the items were determined, the questionnaire was distributed to the research sample. Then, using the SPSS program, the paragraphs were statistically analyzed. It was found that artificial intelligence plays a role in developing the academic level of social science students, with high and medium levels, and that males showed greater development than females. Fourth-grade students had higher levels of knowledge in using artificial intelligence compared to their third-grade peers. However, there was no statistically significant difference between the average scores of the study sample members regarding the role of artificial intelligence in cognitive development according to gender and educational level, as it was not statistically significant at the statistical significance level (0.05). In light of the results, some recommendations and proposals were presented. Keywords: artificial intelligence, teaching process, cognitive level, types of artificial intelligence, social sciences department.
Keywords: Artificial Intelligence; Teaching Process; Cognitive Level; Types of Artificial Intelligence; Department of Social Sciences